Three tier shared spectrum, shared infrastructure, and a path to 5G - Marshall, Preston (Cambridge : Cambridge University Press, 2017)
Written by a leading expert in the field, this unique book describes the technical requirements for three-tier shared spectrum as well as key policy rationale and the impact for 5G. Detail is provided on the inception of the concept and its implementation in the US Citizens Broadband Radio Service (CBRS), along with descriptions of standards for deployment, algorithms required for implementation, and the broader consequences for wireless network and service architectures. The economic and innovation incentives offered by three-tier spectrum are described, along with potential outcomes such as widely deployed neutral host networks. There is also detailed technical analysis of the unique challenges introduced by three-tier spectrum, such as co-existence among non-cooperating networks. Covering a wide range of spectrum bands, International Telecommunication Union (ITU) international allocations, and rule structures that can be adapted for different regimes, this is ideal for an international readership of communications engineers, policy-makers, regulators, and industry strategic planners.
Title from publisher's bibliographic system (viewed on 30 Aug 2017).
Keywords: Radio resource management (Wireless communications); Computer network architectures